Clinical characteristics, outcome, and therapeutic effect of tafamidis in wild‐type transthyretin amyloid cardiomyopathy - Seiji Takashio; Mami Morioka; Masanobu Ishii; Kei Morikawa; Kyoko Hirakawa; Shinsuke Hanatani; Fumi Oike; Hiroki Usuku; Masafumi Kidoh; Seitaro Oda; Eiichiro Yamamoto; Kenichi Matsushita; et al. (ESC Heart Failure, 2023)
Abstract Aims Tafamidis improves prognosis in patients with transthyretin amyloid cardiomyopathy (ATTR‐CM). However, real‐world data on the therapeutic effect of tafamidis are lacking. This study aimed to evaluate the clinical course, outcomes, and effectivity monitoring of the therapeutic effect of tafamidis in patients with ATTR‐CM. Methods and results This is a single‐centre, retrospective observational study. We evaluated the clinical characteristics and outcomes in 125 consecutive patients with wild‐type ATTR‐CM (ATTRwt‐CM) treated with tafamidis (treatment group) and 55 untreated patients (treatment‐naïve group). We monitored the therapeutic effect of tafamidis for 12 months by evaluating serial cardiac biomarker and imaging findings. The treatment group had significantly more favourable outcome in all‐cause mortality and hospitalization due to heart failure than the treatment‐naïve group in both the entire cohort (P < 0.01) and the propensity score‐matched cohort (P < 0.05). Kaplan–Meier survival curves showed that tafamidis treatment significantly reduced all‐cause mortality (P = 0.03, log‐rank test), with the curves diverging after approximately 18 months of treatment in the propensity score‐matched cohort. On inverse probability of treatment weighting analysis, tafamidis treatment showed a reduced all‐cause mortality [hazard ratio (HR), 0.31; 95% confidence interval (CI), 0.11–0.93; P = 0.04]. High‐sensitivity cardiac troponin T (hs‐cTnT) > 0.05 ng/mL, B‐type natriuretic peptide (BNP) > 250 pg/mL, and estimated glomerular filtration rate (eGFR) < 45 mL/min/1.73 m2 scored 1 point each. Multivariate logistic regression analysis revealed that a high score (2–3 points) was a significantly poor prognostic factor of composite clinical outcomes, including all‐cause death and hospitalization for heart failure (HR, 1.55; 95% CI, 1.22–1.98; P < 0.01) for patients in the treatment group. After 12 months of tafamidis treatment, hs‐cTnT levels decreased significantly [0.054 (0.036–0.082) vs. 0.044 (0.033–0.076); P = 0.002], with no significant changes in BNP levels, echocardiographic parameters, native T1 value, and extracellular volume fraction on cardiac magnetic resonance imaging. Conclusions The prognosis of patients with ATTRwt‐CM treated with tafamidis was more favourable than that of untreated patients. Patient stratification combined with biomarkers (hs‐cTnT, BNP, and eGFR) predicted clinical outcomes. hs‐cTnT may be a useful biomarker for evaluating the therapeutic effect of tafamidis.